Creeping suprapubic catheter site growth-a unique presentation in a case of carcinoma prostate - A. V. B., Krishnakanth; Shah, Abhijit; K. S., Chaitanya; Hegde, Padmaraj (International Journal of Research in Medical Sciences, 2024)
Postoperative spindle cell nodule (PSCN) is a scarcely studied benign histopathological variant of prostatic growth. This case report demonstrates an extensive growth arising from the suprapubic cystostomy site in the background of carcinoma prostate. An 82-year-old gentleman, diagnosed with primary carcinoma of prostate who underwent channel transurethral resection of prostate (TURP) and subsequent suprapubic catheterisation (SPC) in view of acute retention at a later time period, presented with an exophytic ulcer-proliferative growth along the SPC. The unique presentation as described in our case report, poses a diagnostic conundrum that requires a mention in the literature. Edge wedge biopsy of the lesion revealed it to be a spindle cell neoplasm. The unique case of SPC site involvement by prostatic growth raises questions about the nature of any such growth, with a possibility of it being benign growth and an excellent long-term prognosis for such patients with regard to the PSCN.